2012
DOI: 10.1016/j.cell.2012.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 Exploits a Pre-Existent Enhancer Landscape for Regulatory T Cell Lineage Specification

Abstract: Summary Regulatory T (Treg) cells, whose identity and function are defined by the transcription factor Foxp3, are indispensable for immune homeostasis. It is unclear whether Foxp3 exerts its Treg lineage specification function through active modification of the chromatin landscape and establishment of new enhancers or by exploiting a pre-existing enhancer landscape. Analysis of the chromatin accessibility of Foxp3-bound enhancers in Treg and Foxp3-negative T cells showed that Foxp3 was bound overwhelmingly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
453
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(510 citation statements)
references
References 54 publications
57
453
0
Order By: Relevance
“…2) showed that FOXP3 is not the unique and dominant driver of the network, in keeping with the now accepted notion that FOXP3 is a key important player but not the unique player in Treg signature specification. Some of this association likely reflects the importance of FOXP3 in controlling the expression of Treg signature genes, and many of these (e.g., CTLA4, TRIB1, RTKN2, IKZF2) are direct FOXP3 targets in mouse cells (14). Others may actually be direct regulators of FOXP3 transcription or of protein stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) showed that FOXP3 is not the unique and dominant driver of the network, in keeping with the now accepted notion that FOXP3 is a key important player but not the unique player in Treg signature specification. Some of this association likely reflects the importance of FOXP3 in controlling the expression of Treg signature genes, and many of these (e.g., CTLA4, TRIB1, RTKN2, IKZF2) are direct FOXP3 targets in mouse cells (14). Others may actually be direct regulators of FOXP3 transcription or of protein stability.…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts most correlated with FOXP3 MFI likely include direct FOXP3 targets, or conversely encode factors that regulate FOXP3 itself. As evidence for the former, genes with highest absolute correlation to FOXP3 MFI were also enriched in FOXP3-binding sites (extrapolating from FOXP3 binding to orthologs in mice) (14). FOXP3-correlated transcripts include CCR8, a marker of Treg cells with higher FOXP3 levels (51), but also genes that do not belong to the Treg signature such as CD101, which has been associated with Treg potency (52).…”
Section: Treg Tconvmentioning
confidence: 99%
“…In general, selective cytokine receptor or SOCS protein expression serves as a major buffer to resist cytokine-driven repolarization of T cells, although DNA accessibility (discussed next) also has a crucial role. Second, the so-called 'master regulators' or 'lineage-defining' transcription factors T-bet, GATAbinding protein 3 (GATA3), RORγt, BCL-6 and FOXP3 have a substantial, but often incomplete, role in setting the transcriptional programmes of T H 1, T H 2, T H 17, T FH and T Reg cells, respectively 62,[113][114][115] . The capacity for these transcription factors to directly antagonize each other's functions through direct protein-protein interactions may impart coherency in effector responses 11,116 (FIG.…”
Section: Box 2 | Phenotypic Plasticity In Inflammatory and Regulatorymentioning
confidence: 99%
“…Genome‐wide mapping of epigenetic variation in Treg and conventional T‐cells reveals cell type‐specific transcriptional activity,83, 96 and large‐scale cataloguing of the marks associated with active, open or closed chromatin has opened the way for understanding cell type‐specific gene regulation (e.g. epigenomics roadmap,97, 98 FANTOM99, 100, 101, 102).…”
Section: Genetic Risk Of Autoimmune Disease Alters Treg Functionmentioning
confidence: 99%